Environmental economics in social and environmental projects: disclosure of investments by Petrobras company in the year 2012 - Vargas, Sedenir Antonio de; Bonzanini, Osmar Antonio; Vargas, Alzenir José de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This article addresses issues related to social, environmental and economic issues in business, considering its importance to society and organizations. The concern with social and environmental issues is the whole society and in this context are the companies, the need to act in the community where they operate. Initially it was necessary to review the theoretical issues here involved, through a literature exploratory, conceptualize and reflect on the importance of environmental accounting, of social responsibility, related to thesustainability for businesses of economic bias. Posteriorly, information of company Petrobras are presented in order to identify social and environmental projects, which are highlighted in the reports of directors and sustainability of the company for theyear 2012. Subsequently presents the investments made by the company in such projects, quantifying the amount of resources invested. The main results show that there is a concern of the company and its commitment in relation to social and environmental issues, as well as the purpose of reducing the impacts of your business on the environment and society through the application of financial resources from its activities.